Project Based Learning Dengan Pembelajaran Berdiferensiasi Sebagai Upaya Peningkatan Hasil Belajar Siswa - Dwi Putra Andika; Raynaldy Farishtya Syafiq; Bagus Fajar Tantowi; Renny Dwijayanti; Istilahwati Istilahwati (Departement of Mathematics Education, 2024)
Currently, the world is entering the era of Society 5.0, which will impact student learning due to the proliferation of technology that facilitates easy access to learning materials. If teachers rely solely on lecture methods, students may become bored and less active in the learning process. One suitable instructional model for this era is project-based learning. This approach teaches students to engage in practical activities and take responsibility for specific tasks, providing them with direct experience rather than just theoretical knowledge. The purpose of this study is to explain the impact of implementing project-based learning combined with differentiated instruction on student learning outcomes. The research method used is classroom action research, divided into two cycles. The stages include initial planning, followed by action, observation, and finally, reflection. The results of this study indicate that the application of the project-based learning model, coupled with differentiated instruction, is effective in improving student learning outcomes.